The Development of Learning Videos Using Wondershare Filmora Software on Human Reproductive System Material - Irfan Ihza Wardana; Nur Rahayu Utami (Journal of Biology Education, 2023)
The Covid-19 pandemic has changed the way people live, including in the field of education. One of them is WFH (work from home), which causes the learning process to be carried out from home by online. Students found it difficult to understand the material during online learning which caused learning outcomes to decrease. On the other hand, the development of technology and information can be used so that it is beneficial for education. The advantages of learning video media greatly assist the teacher in conveying the material to be delivered and students better understand the material presented by the teacher. For this reason, it was necessary to develop video-based media for learning the Reproductive System material. The purpose of this study was to analyze the validity, feasibility, and influence of media effectiveness on student learning outcomes based on learning videos on the Reproductive System material. The research steps that were passed used the 4D development model, namely Define, Design, Development, and Disseminate. The research instruments used were student questionnaire sheets, interview sheets, validity sheets, teacher and student response questionnaire sheets, as well as pre-test/post-test sheets. The results of research on the Reproductive System learning video media have met the criteria of being very valid by media experts at 98% and valid by material experts with a score of 72%, the media feasibility score is 94% or very feasible by a questionnaire of teachers and students, and learning video media is effective in improving results student learning on the subject of the Human Reproductive System at SMA Negeri 1 Banjarnegara.